Modifikasi Permainan Bowling dalam Meningkatkan Kemanpuan Membilang pada Anak Tunagrahita Ringan - Syahri, Rizka Purnama; Ardisal, Ardisal; Irdamurni, Irdamurni; Triswandari, Retno; Nasri, Yosa Yulia (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to improve the numeracy ability of mildly impaired students at SLB Negeri 1 Lubuk Sikaping through the modification of bowling games. This study uses a quantitative research type through an experimental approach in the form of Single Subject Research (SSR) and applies an A-B-A design. There are two variables in this study, namely the modification of bowling games as an independent variable and the ability to count as a bound variable. The subject of this study was a mentally retarded student with the initials D, male in class IV-C SLB Negeri 1 Lubuk Sikaping who was not yet able to count numbers up to 20 even though he was already in class IV. To overcome this problem, the researcher aims to improve the ability to count in students by continuing the ability of students who were previously only able to count 1 to 10 continued by counting 11 to 15 through modification of the bowling game. The results of the study showed the percentage of results in the Baseline condition (A1) with a percentage of 33%, 33%, 33%, 33%. Intervention Condition (B) with percentages of 40%, 40%, 67%, 73%, 87%, 93%, 93%, 93%. For Baseline condition (A2) with percentages of 87%, 93%, 93%, 93%. The final data that has been analyzed will be in the form of percentages and visual graphs, and it can be concluded that bowling game modification can improve the ability to count numbers in mentally retarded children